Reformas e ampliações em edificações unifamiliares: estudo de caso - Bottega, Edivaldo Aparecido (2023)
The concern with disasters in Civil Construction has gained strength in recent decades through the search for improvements and care in renovations and expansions. When this subject is related to the technical standards (NBRs), the need to develop new regulations that manage the technical and professional procedures of Civil Construction is evident. Currently, only one technical standard is directly related to this topic, "NBR 16280 – Buildings Reforms – Renovation Management Systems – Requirements," published in 2014, which is more concerned with condominiums. This work sought to develop research on renovations and expansions in single-family buildings, carrying out a theoretical study on the referred norm and conceptualizing the prevention and care in these environments. To this end, a survey was first conducted on renovations in some neighborhoods in Campo Mourão (PR) to identify the knowledge about the norms for carrying out renovations. A form was applied to the renovations' owners and executors to verify both parties' training and knowledge about the NBR 16280:2014. After this survey, it was found that most of the renovations did not have projects or follow-up by qualified professionals and that although 83% of the interviewees declared to be aware of a technical standard existence that regulates the activities of renovations and expansions, only 33% declared to know its content. Among the renovations addressed, one was chosen as a case study considering the owner's permission, low financial conditions, and the author's commute to the site. The results showed that the owners have, for the most part, only a structural design of the renovation, which an engineer or architect does not accompany. On the other hand, the executors, in their totality, have been working in the field for an extended period and in various construction areas. However, they do not have any training in the area. In addition, owners and executors know there is a norm for renovations but do not know its content or what is required. An on-site technical follow-up of a renovation documented several changes made over time, which were not professionally monitored. Thus, it is concluded that there is a need for a technical standard also applied to single-family buildings and that there should be greater supervision in this type of work to demand the correct procedures.